2020
DOI: 10.1111/os.12776
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Anterior Shoulder Dislocation by Coracoid Osteotomy with or without Bristow–Latarjet Procedure

Abstract: Objective: To investigate the clinical efficacy and outcomes of the coracoid osteotomy with or without Bristow-Latarjet procedures in the treatment of chronic anterior shoulder dislocation (CASD). Methods: Between January 2013 and January 2019, 20 shoulders of 18 patients who were diagnosed with chronic anterior dislocation and underwent open reduction in our trauma center were retrospectively studied. Open coracoid osteotomy with Bristow-Latarjet procedures were performed on 16 shoulders and open coracoid ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The result was agreed with results attained by Yang et al (12) who reported that the range of motion (ROM) and the shoulder functional evaluation (visual analogue scale [P< 0.001], American shoulder and elbow surgeon's score [P< 0.001], and UCLA score [P< 0.001]) in patients who underwent Bristow-Latarjet procedures were significantly improved. However, Moroder et al (13) reported that Strength and range of motion showed no significant differences except for diminished internal rotation capacity in the Latarjet group at every follow-up time point (P < .05).…”
Section: Discussionsupporting
confidence: 90%
“…The result was agreed with results attained by Yang et al (12) who reported that the range of motion (ROM) and the shoulder functional evaluation (visual analogue scale [P< 0.001], American shoulder and elbow surgeon's score [P< 0.001], and UCLA score [P< 0.001]) in patients who underwent Bristow-Latarjet procedures were significantly improved. However, Moroder et al (13) reported that Strength and range of motion showed no significant differences except for diminished internal rotation capacity in the Latarjet group at every follow-up time point (P < .05).…”
Section: Discussionsupporting
confidence: 90%
“… 5 Open reduction of neglected anterior dislocations has been safely performed with variable outcomes. 1 , 4 , 9 The arthroscopic technique of relocating a missed anterior shoulder dislocation presented in this article has several advantages. Patients of the older age group and with osteoporotic bones are at increased risk of a surgical humeral neck fracture during forceful closed reductions.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that operative intervention combined with meticulous physiotherapy contributes to a favourable outcome. Yang et al did a retrospective study on 20 shoulders of 18 patients, of whom 16 were managed by Latarjet procedure and four patients by Bristow procedure[15]. They found that there was a significant improvement in range of motion, VAS score, UCLA score, and American Shoulder and Elbow Surgeons (ASES) score in all the patients.…”
mentioning
confidence: 99%